The anti-obesogenic and anti-diabetic properties of marine collagen peptides - Wong, Rina P. M.; Zhou, Zhong Kai; Strappe, Padraig M. (Frontiers in Food Science and Technology, 2024)
Obesity has reached epidemic proportions in the world and is increasing rapidly as traditional diets are replaced by more readily available processed and high fat content foods. Obesity is a complex condition with several drivers which can influence a person’s weight, this results in a number of co-morbidities including cardiovascular disease and type 2 diabetes. In Australia, it is estimated that over 66.97% of adults are overweight or obese and this is increased further in regional and remote communities (obesity evidence Hub). According to the World Health Organization 2016 report, 1.9 billion adults were overweight with an estimated 650 million being obese (WHO). In Australia, it is estimated that 1.3 million people have type 2 diabetes, and WHO estimates that around 422 million people have diabetes (WHO).